Space‐confined microwave synthesis of ternary‐layered BiOCl crystals with high‐performance ultraviolet photodetection - Kang, Lixing (2020)
In recent years, two‐dimensional (2D) ternary materials have attracted wide attention due to their novel properties which can be achieved by regulating their chemical composition with a very great degree of freedom and adjustable space. However, as for the precise synthesis of 2D ternary materials, great challenges still lie ahead that hinder their further development. In this work, we demonstrated a simple and reliable approach to synthesize 2D ternary‐layered BiOCl crystals through a microwave‐assisted space‐confined process in a short time (<3 minutes). Their ultraviolet (UV) detection performance was analyzed systematically. The photodetectors based on the as‐obtained BiOCl platelets demonstrate high sensitivity to 266‐nm laser illumination. The responsivity is calculated to be ∼8 A/W and the response time is up to be ∼18 ps. On the other hand, the device is quite stable after being exposed in the ambient air within 3 weeks and the response is almost unchanged during the measurement. The facile and fast synthesis of single crystalline BiOCl platelets and its high sensitivity to UV light irradiation indicate the potential optoelectronic applications of 2D BiOCl photodetectors.